High carbon load in food processing industrial wastewater is a driver for metabolic competition in aerobic granular sludge - Paulo, Ana M. S. (2021)
The Supplementary Material for this article can be found online at: https://www.frontiersin.org/articles/10.3389/fenvs.2021.735607/ full#supplementary-material